As diásporas maranhenses Codó: caminhos e descaminhos de um povo em movimento (1970-2010) - Sousa, José Reinaldo Miranda de (2016)
Diasporas represented a constant in the history of people of Maranhão. Since the colonial period, several people landed there: French, Dutch, Portuguese and in large numbers, Africans, all these people with their unique cultures, making today in Maranhão a hybrid society. This entry of several people in its territory has several cycles and extends to the 1960s, when Brazil underwent profound political and economic changes, which inserted Maranhão in the military project context. This study is aimed at the contemporary diaspora in the state’s middle-eastern region, more precisely in the municipality of Codó. It is observed how this phenomenon occurred, since the implanted agrarian policy from the "Sarney Land Law", which imposed major changes to the lands structure, i.e. a policy with bases in developmental design that favored big businesses, south and southeast businessmen and multinational capital. This restructuring has affected the general population, especially the inhabitants of the land in common use, removing them from their lands, also causing the intensification of land conflicts in the state. This research studies, from the perspective of cultural history, the diasporic process experienced by these subjects; Their memories in new territories and the construction of their identities; The paths, the waywardness and the changes occurring in that community as a result of this displacement. They will be analyzed from a group of migrants from Codó living in Aurora Garden, Guaianases, eastern region of the city of São Paulo, their struggles and achievements in the state territory and the strengthening of their cultures and identities, in this "Codó inside Guaianases". Investigated as the agricultural model imposed from the 1970s, he promoted the diasporic process that has lived up to the present day the maranhense rural population